Bone marrow fat content is correlated with hepatic fat content in paediatric non-alcoholic fatty liver disease. Issue 5 (May 2017) - Yu, N.Y.; Wolfson, T.; Middleton, M.S.; Hamilton, G.; Gamst, A.; Angeles, J.E.; Schwimmer, J.B.; Sirlin, C.B.
Abstract : Aim: To investigate the relationship between bone marrow fat content and hepatic fat content in children with known or suspected non-alcoholic fatty liver disease (NAFLD). Materials and methods: This was an institutional review board-approved, Health Insurance Portability and Accountability Act (HIPAA)-compliant, cross-sectional, prospective analysis of data collected between October 2010 to March 2013 in 125 children with known or suspected NAFLD. Written informed consent was obtained for same-day research magnetic resonance imaging (MRI) of the lumbar spine, liver, and abdominal adiposity. Lumbar spine bone marrow proton density fat fraction (PDFF) and hepatic PDFF were estimated using complex-based MRI (C-MRI) techniques and magnitude-based MRI (M-MRI), respectively. Visceral adipose tissue (VAT) and subcutaneous adipose tissue (SCAT) were quantified using high-resolution MRI. All images were acquired by two MRI technologists. Hepatic M-MRI images were analysed by an image analyst; all other images were analysed by a single investigator. The relationship between lumbar spine bone marrow PDFF and hepatic PDFF was assessed with and without adjusting for the presence of covariates using correlation and regression analysis. Results: Lumbar spine bone marrow PDFF was positively associated with hepatic PDFF in children with known or suspected NAFLD prior to adjusting for covariates ( r =0.33, p =0.0002). Lumbar spine bone marrow PDFF was positively associated with hepatic PDFF in children with known or suspected NAFLD ( r =0.24, p =0.0079) after adjusting for age, sex, body mass index z -score, VAT, and SCAT in a multivariable regression analysis. Conclusion: Bone marrow fat content is positively associated with hepatic fat content in children with known or suspected NAFLD. Further research is needed to confirm these results and understand their clinical and biological implications. Highlights: Bone marrow PDFF is positively correlated with hepatic PDFF in pediatric NAFLD. The correlation is independent of age, sex, BMI z-score, VAT, and SCAT. Our understanding of the association between NAFLD and low BMD is advanced. This study may contribute to preventing osteoporosis later in life.